Dementia and occupational exposure to organic solvents. Issue 10 (October 1998) - Palmer, K; Inskip, H; Martyn, C; Coggon, D
Abstract : OBJECTIVES: To investigate whether occupational exposure to organic solvents increases the risk of dementia. METHODS: Cases of dementia were identified from the computed tomography records of eight neuroradiology centres in England and Wales, and were compared with two sets of controls investigated at the same centres. The first set of controls were patients with brain cancer and the second set were patients with other disorders that were not chronically disabling. Lifetime occupational histories were obtained through a postal questionnaire completed by the subjects or their next of kin. Associations between dementia and occupation were examined by logistic regression. RESULTS: Usable questionnaires were returned for 204 (61%) of the cases, 225 (51%) of the controls with brain cancer, and 441 (61%) of the other controls. The findings with each of the two sets of controls were similar. In comparison with all controls combined, cases had less often worked ever as a painter or printer (odds ratio (OR) 0.6, 95% confidence interval (95% CI) 0.3 to 1.2), and were less likely to have worked for > 1 year as a printer, painter, or launderer or dry cleaner (OR 0.6, 95% CI 0.3 to 1.4). CONCLUSIONS: These findings provide no support for the hypothesis that occupational exposure to solvents is a cause of dementia. An excess risk in subsets of workers with extremes of exposure cannot be discounted, but the data indicate that any influence of exposure to solvents on the overall incidence of severe dementia in the general population of England and Wales is small.